2023
DOI: 10.1007/s10934-023-01458-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic hydroxyethyl cellulose spheres with efficient congo red removal

Abstract: Ecofriendly adsorbent materials for the rapid and efficient removal of pollutant dyes are highly desired on account of concerns about environmental pollution and human health. Herein, novel magnetic HC/Fe3O4 spherical materials have been constructed via crosslinking hydroxyethyl cellulose (HC) by poly(ethylene glycol) diglycidyl ether (PGDE) followed by the introduce of magnetic Fe3O4 by a facile and effective strategy developed in this work. The morphology, structure and magnetic behavior of the spherical mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…In our previous investigations, we demonstrated that adsorbents based on polymers exhibit high efficiency in the removal of heavy metals (e.g., Pb 2+ , Cu 2+ ) [12]. These adsorbents also effectively remove dye pollutants from aqueous solutions [19,20]. Therefore, adsorption is an efficient and friendly method for the removal of heavy metals and dyes from aqueous solutions, and substantial attention has been directed towards advancing adsorption materials, encompassing carbon-based hydrogels [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous investigations, we demonstrated that adsorbents based on polymers exhibit high efficiency in the removal of heavy metals (e.g., Pb 2+ , Cu 2+ ) [12]. These adsorbents also effectively remove dye pollutants from aqueous solutions [19,20]. Therefore, adsorption is an efficient and friendly method for the removal of heavy metals and dyes from aqueous solutions, and substantial attention has been directed towards advancing adsorption materials, encompassing carbon-based hydrogels [21,22].…”
Section: Introductionmentioning
confidence: 99%